A história da Escola Estadual de Segundo Grau Dr. Dario Pacheco Pedroso: sua origem, inserção social e impacto no percurso profissional dos alunos (1970 - 1994) - Matos, Ana Rita Bueno de Camargo (2017)
This study aims to study the Secondary School of Doctor Dario Pacheco Pedroso, created in 1970 in Taquarivaí, then Itapeva district, São Paulo and incorporated in 1994 to the State Center of Technological Education Paula Souza. This object is analyzed from the historical trajectory of agricultural education in Brazil, from the Municipality, where the school was installed and from the school itself, aiming to understand its administrative organization and the pedagogical proposal developed by the institution. The results show that agricultural education underwent changes, according to educational policies, elaborated according to the demands of each historical context. It was during the period of the military civil dictatorship in Brazil, in the scenario of conservative modernization, that the institution analyzed here was created. The implementation of technical courses in agriculture contributed to the formation of skilled labor in the Taquarivai region, enabling its development and participation in the process of agricultural expansion in the state of São Paulo, as well as influencing the professional growth of students graduates